2017
DOI: 10.1177/1541931213601595
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Workstations: Magic Pills for Office Worker Health?

Abstract: Routine office or computer work are of public health concerns due to their sedentary nature. Sit- stand desks may be prescribed for employees based on medical or ergonomic factors. Sit-stand or active workstations, either assigned to individual workers or made available in “unassigned” office areas are also making inroads into the workplace with the goal of reducing sedentary work, varying (alternating) work postures, improving productivity, or accommodating workers with musculoskeletal symptoms. This diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Biomechanical data are essential to help the ergonomic study of a product or environment, as they can help to highlight and to quantify causes of perceived discomfort of system users [8]. For instance, Lin et al [9] evaluated the biomechanics of the standing and sitting positions workers used during working time, identifying that different postures adopted for the shoulder and forearm between workstations and the presence of greater postural variability in the standing position increase shoulder rotation and extension patterns that could be associated with working problems. Harari et al [10] investigated worker biomechanics during multi-task manual materials handling in order to develop a predictive model for the moments acting on the worker's body and its joint angles during those tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical data are essential to help the ergonomic study of a product or environment, as they can help to highlight and to quantify causes of perceived discomfort of system users [8]. For instance, Lin et al [9] evaluated the biomechanics of the standing and sitting positions workers used during working time, identifying that different postures adopted for the shoulder and forearm between workstations and the presence of greater postural variability in the standing position increase shoulder rotation and extension patterns that could be associated with working problems. Harari et al [10] investigated worker biomechanics during multi-task manual materials handling in order to develop a predictive model for the moments acting on the worker's body and its joint angles during those tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by Kang and Kim [ 21 ] and Wendsche and Lohmann-Haislah [ 22 ] showed that modern people are able to mentally recover from work stress through Other Things, namely, non-working hours, and that thoughts of leisure activities help solve actual psychological and emotional problems. Employees were found to perceive doing Other Things as having a positive effect on conducting work tasks, stating that they “improve work efficiency by providing moderate rest” and “promote close relationships with colleagues” [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%